PENGEMBANGAN APLIKASI MAGANG MAHASISWA UNTUK MEMBANTU PROSES ADMINISTRASI - Nyimas Sopiah; Msy Al Maudina (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
There are several types of internship activities at Bina Darma University, namely, internship activities where students propose partners directly to the Head of the Study Program and there is also a Certified Student Internship Program (PMMB) organized by the Indonesian Human Capital Forum (FHCI). So far, information on the Certified Student Internship Program (PMMB) that students get is still conventional and makes it difficult for the Head of the Alumni and Tracer Study Unit where data collection and registration are taken care of directly by the Head of the Alumni and Tracer Study Unit. Therefore the author in this case makes an apprenticeship application using the web engineering method. This application can be accessed and used by Bina Darma University alumni and Tracer Study unit heads, Study Program Heads, Lecturers and also Bina Darma Students, and it is hoped that this system can help and expand opportunities for students who wish to take part in the Certified Student Internship Program (PMMB).